Releasing number of Telenomus remus (Nixon) (Hymenoptera: Platygastridae) against Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) in corn, cotton and soybean - Pomari, Aline Farhat; Bueno, Adeney de Freitas; Oliveira de Freitas Bueno, Regiane Cristina [UNESP]; Menezes Junior, Ayres de Oliveiras; Prado Fernandes Fonseca, Augusto Cesar (Univ Federal Santa Maria, 2013)
Telenomus remus releasing numbers may vary depending on the crop, plant architecture and/or the plant phenological stage. Thus, we examined the number of parasitoids needed for effective pest control of Spodoptera frugiperda on corn, cotton and soybean. In all crops, the parasitism response in relation to increasing numbers of the parasitoids had a quadratic effect. In corn, the maximum parasitism observed was 99.8% and 96.8% at a parasitoid releasing number of 0.231 and 0.264 T. remus females per S. frugiperda egg at phenological stages V-4 and V-10, respectively. Differently, in cotton and soybean, the highest parasitim were recorded using the highest tested T. remus releasing numbers (0.297 parasitoid per S. frugiperda egg). In cotton, it was 77.8% and 73.1% at the vegetative and reproductive stages, respectively and in soybean, it was 77.3% and 54.4% also at the vegetative and reproductive stages. Thus, the appropriated T. remus releasing number might vary accordingly to the crop and plant phenological stage, being higher for soybean and cotton and lower for corn.
Keywords: biological control; parasitoid density; parasitism